2009
DOI: 10.1038/pcan.2009.24
|View full text |Cite
|
Sign up to set email alerts
|

Androgens induce oxidative stress and radiation resistance in prostate cancer cells though NADPH oxidase

Abstract: Androgen deprivation therapy (ADT) facilitates the response of prostate cancer (PC) to radiation. Androgens have been shown to induce elevated basal levels of reactive oxygen species (ROS) in PC, leading to adaptation to radiation-induced cytotoxic oxidative stress. Here, we show that androgens increase the expression of p22 phox and gp91 phox subunits of NADPH oxidase (NOX) and ROS production by NOX2 and NOX4 in PC. Pre-radiation treatment of 22Rv1 human PC cells with NOX inhibitors sensitize the cells to rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 31 publications
1
47
0
Order By: Relevance
“…ROS and Nox (a ROS generator), have been reported to regulate cell proliferation, progression, metastasis and radiation resistance of prostate cancer cells (3335). Our cDNA microarray data revealed that Nox5 was up-regulated in overexpressing SREBP-1 prostate cancer cells compared to control cells (unpublished data).…”
Section: Resultsmentioning
confidence: 99%
“…ROS and Nox (a ROS generator), have been reported to regulate cell proliferation, progression, metastasis and radiation resistance of prostate cancer cells (3335). Our cDNA microarray data revealed that Nox5 was up-regulated in overexpressing SREBP-1 prostate cancer cells compared to control cells (unpublished data).…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study, Lu et al demonstrate that Nox4 is involved in androgen-induced oxidative stress and radiation resistance in prostate cancer cells [42]. This androgen-induced ROS production and radioresistance in prostate cancer cells are mediated via Nox2 and Nox4, and the inhibition of Nox by apocynin can sensitize in vitro tumor cells to radiation.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, manipulating the intracellular redox state might potentially serve as a strategy for increasing their sensitivity to chemotherapeutic drugs or irradiation. In prostate cancer cells, it has been shown that androgen can induce elevated basal levels of ROS, thereby resulting in adaptation to radiation-induced cytotoxic stress (Lu et al, 2010). It is noteworthy that androgen-induced ROS generation in prostate cancer cells was dependent on Nox2 and Nox4; preradiation treatment with Nox inhibitors sensitized the cells to radiation-induced cytotoxicity (Lu et al, 2010).…”
Section: Cancer Cell Survival and Proliferationmentioning
confidence: 99%
“…In prostate cancer cells, it has been shown that androgen can induce elevated basal levels of ROS, thereby resulting in adaptation to radiation-induced cytotoxic stress (Lu et al, 2010). It is noteworthy that androgen-induced ROS generation in prostate cancer cells was dependent on Nox2 and Nox4; preradiation treatment with Nox inhibitors sensitized the cells to radiation-induced cytotoxicity (Lu et al, 2010). In another study, stable expression of the constitutively active mutant V12-H-Ras in virus transformed human lung cells dramatically increased intracellular production of superoxide via activation of Nox and induced resistance to TNF-␣-mediated apoptosis (Liu et al, 2001).…”
Section: Cancer Cell Survival and Proliferationmentioning
confidence: 99%